1998
DOI: 10.1177/000841749806500407
|View full text |Cite
|
Sign up to set email alerts
|

The Occupational Performance History Interview: Evidence for Three Underlying Constructs of Occupational Adaptation

Abstract: The Occupational Performance History Interview (OPHI) was developed to gather data on a person's past and current occupational functioning. The OPHI includes both a life history narrative component designed to render the life history from the client's perspective and a rating scale designed to measure the client's past and present occupational adaptation. Previous research documented the reliability of the OPHI, but there has been limited study of its construct validity. This study used Rasch analysis to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
5
19
0
Order By: Relevance
“…In developing the Relative Mastery Measurement Scale, George, Schkade, and Ishee (2004) emphasized the use of self-selected activities to increase engagement and increase awareness of new or modified responses to environmental demands as key features of the occupational adaptation process. In developing the Occupational Performance History Interview, Mallinson, Mahaffey, and Kielhofner (1998) also found the influence of the environment to be strong enough to warrant its assessment as a unique construct of the occupational adaptation process.…”
Section: Thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In developing the Relative Mastery Measurement Scale, George, Schkade, and Ishee (2004) emphasized the use of self-selected activities to increase engagement and increase awareness of new or modified responses to environmental demands as key features of the occupational adaptation process. In developing the Occupational Performance History Interview, Mallinson, Mahaffey, and Kielhofner (1998) also found the influence of the environment to be strong enough to warrant its assessment as a unique construct of the occupational adaptation process.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Occupational adaptation was defined in the literature as an ongoing, non-linear process to achieve a desired sense of self (Lexell, Iwarsson, & Lund, 2011); a manner of developing a sense of competence, self-efficacy, and identity in occupational participation (Johansson & Isaksson, 2011;Yazdani, 2011;Crist et al, 2005;Firfirey & Hess-April, 2014); and a manner of reframing identity, competence, the environment, and the fit between all three (Klinger, 2005;Mallinson, Mahaffey, & Kielhofner, 1998). In addition, Luck and Beagan (2015) asserted the reciprocal process between occupational adaptation and identity.…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…First, three rating scales are used to generate quantitative data from the interview that are helpful in tracking change over time for individuals. These scales are based on research that identified three underlying constructs (occupational identity, occupational competence, and environmental impact) (Mallinson, Mahaffey, & Kielhofner, 1998). Second, narrative information may be recorded descriptively and visually presented in a narrative slope diagram representing the trajectory of the person's life story.…”
Section: Occupational Performance History Interview: a Narrative-oriementioning
confidence: 99%
“…However, the present study also found that each OCAIRS item has its own unique scale (an unexpected but understandable finding given the unique criteria for rating each item). In contrast, studies of the WRI and OPHI scales, which use a generic format to rate all items, have found that all the items share a common scale (20,21). However, raters using these two scales show greater differences in rater severity (20,21).…”
Section: Discussionmentioning
confidence: 91%